An iron oxyhydroxide-based nanosystem sensitizes ferroptosis by a "Three-Pronged" strategy in breast cancer stem cells. (1st April 2023) - Wu, Kai; Zhang, Wei; Chen, Hao; Wu, Jie; Wang, Xiaotong; Yang, Xinjian; Liang, Xing-Jie; Zhang, Jinchao; Liu, Dandan
Abstract: The anti-apoptotic mechanism of breast cancer stem cells (BCSCs) makes it an obstacle to traditional apoptosis as the primary way of death. Ferroptosis is a recently reported mode of programmed cell death caused by the accumulation of iron-dependent lipid peroxidation (LPO) in cells. High dependence on iron makes BCSCs more sensitive to ferroptosis. However, the high level of the Prominin2 protein and high concentration of GSH in BCSCs make BCSCs able to efflux excess iron ions and clear LPO, which limits the therapeutic efficacy of ferroptosis in BCSCs. To overcome this obstacle, we designed a hyaluronic acid (HA)-coated siProminin2-loaded FeOOH nanoparticle (FeOOH/siPROM2@HA) to amplify ferroptosis. The FeOOH/siPROM2@HA is stable under physiologically neutral conditions but generates Fe 3+ in an acidic microenvironment; meanwhile, the released siProminin2 inhibits its efflux, and then Fe 3+ undergoes a redox reaction with endogenous GSH to produce Fe 2+, which initiates the Fenton reaction-based ferroptosis by LPO elevation. Both in vitro and in vivo studies showed that these pH-sensitive NPs significantly inhibited tumor growth by downregulating glutathione peroxidase 4 (GPX4). Overall, this work demonstrates a "three-pronged" strategy for amplified ferroptotic therapy by simultaneously promoting intracellular iron, inhibiting iron efflux, and depleting GSH, which presents a potential strategy for CSC-targeted cancer therapy. Statement of Significance: As the root of recurrence and metastasis, breast cancer stem cells (BCSCs) are resistant to traditional apoptotic death, so it is urgent to explore a new death mode for BCSCs. It has been reported that BCSCs are highly iron-dependent and, therefore, more sensitive to ferroptosis; however, the therapeutic efficacy is greatly limited by the overexpression of Prominin2 in BCSCs, which is correlated with resistance to ferroptosis by exocytosis of iron ions. In this work, we designed a hyaluronic acid-coated siProminin2-loaded FeOOH nano-drug (FeOOH/siPROM2@HA) to accelerate ferroptosis of BCSCs by simultaneously increasing iron ion content, inhibiting iron efflux, and scavenging GSH. This "three-pronged" strategy has significant implications for BCSC-targeted cancer therapy. Graphical abstract: Image, graphical abstract